2015
DOI: 10.1155/2015/380451
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Ocular Manifestation of Relapsed Chronic Myelogenous Leukemia Presenting as Myeloid Blast Crisis in a Patient on Imatinib Therapy: A Case Report and Review of the Literature

Abstract: Blast phase in chronic myelogenous leukemia (CML) has rarely been reported to involve extramedullary sites like skin, lymph nodes, and central nervous system. Clinical history, characteristic hematologic findings (elevated leukocyte counts, myelocytic predominance, and basophilia), and Philadelphia chromosome are of high diagnostic significance especially in isolated extramedullary presentations. We describe a unique case of CML relapse with blast phase involving the eye. A 66-year-old man with a known diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…The median age was 37.05 years (range 27.5-49), and 67.5 % of patients were male. Most of the cases were initial presentations of CML (33 cases), and only five of them were in relapses 4,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][25][26][27][28][29][30][31][32][35][36][37][39][40][41][42][43][44][45][46][47] . The retina was most often involved, with retinal hemorrhages as the most common finding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median age was 37.05 years (range 27.5-49), and 67.5 % of patients were male. Most of the cases were initial presentations of CML (33 cases), and only five of them were in relapses 4,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][25][26][27][28][29][30][31][32][35][36][37][39][40][41][42][43][44][45][46][47] . The retina was most often involved, with retinal hemorrhages as the most common finding.…”
Section: Resultsmentioning
confidence: 99%
“…Nine presented with unilateral CML-related ophthalmic findings. 12,17,20,22,27,32,33,39,42 Eight of these had unilaterallydecreased of vision, and 1 had normal vision. 12 Thirty-one patients presented with bilateral ophthalmic findings 4,[8][9][10][11][13][14][15][16]18,19,[23][24][25][26][28][29][30][31][32][34][35][36][37][38][40][41][42]44,46 .…”
Section: Discussionmentioning
confidence: 99%
“…The novelty of this case relies on the fact that there are only 10 cases of isolated extramedullary SBC reported so far and only 1 involving the lymph nodes. 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 Moreover, this is the first case of SBC reported so far under nilotinib first-line treatment. In addition, this is among the very few cases, where mutational analysis was undertaken from the affected tissue, and the only one in which a pan-resistant T315I mutation was documented.…”
mentioning
confidence: 64%
“…Table 1 summarizes disease characteristics and outcomes in reported cases of CP CML with extramedullary SBC on first-line treatment with imatinib. 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 Interestingly, a male predominance is noticed and 7/10 cases are <60 years. In contrast to the short interval between imatinib initiation and SBC described in SBC involving the BM, only 3/10 extramedullary SBC reported patients had received imatinib for less than a year up to SBC.…”
mentioning
confidence: 96%
“…The optic nerve is another rare site of CNS invasion ( 17 - 19 ). In an autopsy study, 16% of CML cases showed optic nerve involvement ( 20 ).…”
Section: Discussionmentioning
confidence: 99%